Child and adolescent psychiatry - Goodman, Robert; Goodman, Robert; Scott, Stephen (John Wiley & Sons, 2012)
An introduction to child psychiatry which draws on clinical experience as well as the latest research findings. Child Psychiatry includes many practical tips on successful assessment and treatment techniques